Dancing by the light of the moon : how poetry can transform your memory and change your life - Brandreth, Gyles Daubeney, 1948- (Michael Joseph, an imprint of Penguin Books, 2019)
"Gyles celebrates the finest uses of our English language by handpicking the ultimate anthology of poetry, from the classics, Auden, Wilde, Shakespeare to our all-time favourites, Milligan, McGough and Armitage, to even our most modern works by Rupi Kaur. With so many wonderful poets to choose from this beautiful compendium will become your definitive poetry book to treasure for years to come. He urges us to savour the perfect couplets, delicate words, and clever quips by learning these exquisite poems by heart. By appreciating, memorising and sharing these poems we can begin to increase literacy rates, improve our memories, all the while enriching our lives with the joy of language. Gyles writes emphatically about the beauty, diversity and ingenuity of the language used in these poems, and the way in which they can transform our lives."--Publisher.